3164 Do cancer survivors understand their risk factors for recurrence and the value of coordinated care between an oncologist and a primary care physician? A survey of endometrial and cervical cancer patients - Subhjit Sekhon; Lindsay Kuroki; Graham Colditz (Journal of Clinical and Translational Science, 2019)
OBJECTIVES/SPECIFIC AIMS: To evaluate gaps in knowledge for women who are cancer survivors regarding the impact of comorbidities and lifestyle behaviors on endometrial and cervical cancer risk, and to assess prevalence of established care with a primary care physician (PCP) among patients and evaluate acceptability of referral to a PCP METHODS/STUDY POPULATION: Single institution cross-sectional study examining all women aged 18 or older with a diagnosis of cervical or endometrial cancer who present for care by a gynecologic oncologist at Barnes-Jewish Hospital/Washington University in St. Louis School of Medicine. Patients will be invited to complete a survey specific to cancer diagnosis that includes questions on participant background and sociodemographic information, knowledge of risk factors for their specific cancer site, and whether or not the patient has a primary care provider and the acceptability of referring RESULTS/ANTICIPATED RESULTS: Majority of women will be unaware of how comorbidities affect cancer risk and treatment outcomes. For women without a PCP, we anticipate that they will be accepting towards the notion of being referred to one for establishing care. DISCUSSION/SIGNIFICANCE OF IMPACT: Pilot information from this study will 1. Allow providers to improve cancer survivorship care plans by increasing collaboration between PCPs and oncologists to provide ongoing care, and 2. Afford information for providers on where gaps in knowledge exist so as to better education patients.